1986
DOI: 10.1161/01.hyp.8.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Renal and endocrine response to saline infusion in essential hypertension.

Abstract: SUMMARY To assess the contribution of the renln-angiotensin-aldosterone system and renal hemodynamics to acute renal sodium handling in essential hypertension we studied 21 subjects who had essential hypertension (16 with normal renin, 5 with low renin) and 9 normal subjects. All were in balance on a 10 mEq sodium intake before receiving a small sodium load, 60 mEq intravenously over 1 hour. Hypertensive subjects with low renin showed the anticipated exaggerated natriuresis, which was transient and occurred wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 20 publications
2
23
0
1
Order By: Relevance
“…In contrast, our experiments demonstrated an enhanced ability to excrete an acute salt load in LSD1-deficient mice. This result is consistent with previous studies in humans, where low renin hypertensives hyperexcreted a salt load in contrast to normotensives or non-modulating hypertensives (a normal renin form of salt-sensitive hypertension) (Cottier et al 1958;Krakoff et al 1970;Luft et al 1977;Rydstedt et al 1986;Hollenberg et al 1986). In this study (data not shown) and previously (Pojoga et al 2011b), renin and aldosterone levels were suppressed in LSD1-deficient mice on HS diet, indicating that activation of the RAS is not a driving force for elevated blood pressure.…”
Section: Animal Studiessupporting
confidence: 93%
“…In contrast, our experiments demonstrated an enhanced ability to excrete an acute salt load in LSD1-deficient mice. This result is consistent with previous studies in humans, where low renin hypertensives hyperexcreted a salt load in contrast to normotensives or non-modulating hypertensives (a normal renin form of salt-sensitive hypertension) (Cottier et al 1958;Krakoff et al 1970;Luft et al 1977;Rydstedt et al 1986;Hollenberg et al 1986). In this study (data not shown) and previously (Pojoga et al 2011b), renin and aldosterone levels were suppressed in LSD1-deficient mice on HS diet, indicating that activation of the RAS is not a driving force for elevated blood pressure.…”
Section: Animal Studiessupporting
confidence: 93%
“…In contrast with this hypothesis, the renin response to saline infusion is not completely restored by 3 days of treatment with enalapril, 26 suggesting alternative explanations for the renin behavior. In our opinion, the reduced ANP increase after Ang II infusion could be taken into consideration.…”
Section: Renal and Hormonal Responses To Angiotensin IImentioning
confidence: 83%
“…After blood collection, renal plasma flow was assessed in both hypertensive patients and control subjects according to the method described by Rystedt et al 26 Briefly, at 9 AM, after 1 hour in a supine position, patients had an intravenous catheter installed in the right arm. A control blood sample was obtained, and /j-aminohippurate (PAH) (bolus injection of 8 mg/kg) was infused.…”
Section: P-aminohippurate Infusionmentioning
confidence: 99%
“…There are, however, examples of bimodally distributed, hypertension-related phenotypes such as modulating and nonmodulating sodium sensitivity. 22 It is also encouraging to note that RFLPs for the renin gene have recently been identified in animal models of hypertension. 23 -24 Thus, RFLPs are among the most promising of the future hypertension predictors, not solely because of their potential for forecasting risk, but also because they can frequently serve as effective entries to more in-depth pathophysiologic studies.…”
Section: Genetic Predictorsmentioning
confidence: 96%